2001
DOI: 10.1509/jimk.9.4.1.19941
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Pricing Control in Export Channels: A Governance Perspective

Abstract: In this article, the authors expand traditional channel control models to investigate the value of absorbing pricing decisions within an exporter's decision-making domain. From a governance perspective, pricing control is considered a structured continuum driven by factors both internal and external to the firm. More specifically, the authors investigate the organizational and environmental influences driving pricing control decisions and the impact of pricing control on both the economic and strategic perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 63 publications
(82 reference statements)
3
57
0
1
Order By: Relevance
“…Theodosiou and Katsikeas, 2001). It is generally acknowledged that the macroenvironment (e.g., economic environment) and the micro-environment (e.g., competition intensity) in the foreign market will have a significant influence on the firms' strategies (Chung and Wang, 2007;Myers and Harvey, 2001). Two environmental market factors, namely competitive intensity and environmental characteristics, have been identified as significant influences on strategic decisions (Cavusgil and Zou, 1994).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Theodosiou and Katsikeas, 2001). It is generally acknowledged that the macroenvironment (e.g., economic environment) and the micro-environment (e.g., competition intensity) in the foreign market will have a significant influence on the firms' strategies (Chung and Wang, 2007;Myers and Harvey, 2001). Two environmental market factors, namely competitive intensity and environmental characteristics, have been identified as significant influences on strategic decisions (Cavusgil and Zou, 1994).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Previous research in exporting (Cavusgil, Chan, & Zhang, 2003;Lages & Montgomery, 2005;Myers & Harvey, 2001;Solberg, Stöttinger, & Yaprak, 2006;Sousa & Bradley, 2008; for a comprehensive review, see Tan & Sousa, 2011;Tzokas, Hart, Argouslidis, & Saren, 2000) has focused on export price setting and international price adaptation/standardization. To achieve adequate performance in foreign markets, existing research has highlighted among other influencing factors on export prices, the level of competition in the foreign market (e.g., Cavusgil & Zou, 1994;Lages & Montgomery, 2005;Myers, Cavusgil, & Diamantopoulos, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Three, only economic performance was measured in this analysis. Prior research has suggested the inclusion of non-economic measures as well, such as whether the selected FME mode has (a) met strategic objectives, (b) attained success in developing relationships with overseas marketing intermediaries, (c) responded effectively to competitive pressures, and (d) gained footholds in the target markets (Cavusgil & Zou, 1994;Myers & Harvey, 2001). The use of both economic and non-economic measures can provide a better gauge of a firm's overall performance in the target market.…”
Section: Discussionmentioning
confidence: 99%